Benchmarking Tree-Inspired-Fractal Branching Dendriform Structures From BC to L-System Based Contemporary Structures - Kökçam, Zeynep Gülcan; Sahin, Murat; Gulten, Ayca (My University, 2025)
Nature has its own complex geometry, which couldn’t be explained using traditional methods until the advent of Fractal Geometry. Nowadays, we can observe and represent almost every geometry using quantitative tools. In this study, the compatibility of geometric compositions, referencing Euclidean geometry from hand-drawing environments to digital drawing and computational Computer-aided design (CAD) tools in the architectural products of complex parametric designs, was observed. Historical structures such as Maison Carrée, The Sakyamuni Pagoda of Fogong Temple, Saint Chapelle, Gloucester Cathedral, King’s College Chapel, La Sagrada Familia, and the Stuttgart Airport Terminal, as well as contemporary structures generated by Parametric Design Tools, were examined. Both past and current parametric design examples were benchmarked. The plans and column head views of buildings were analyzed using the Fractal Analysis Method with the FracLac software, which functions as a plug-in within ImageJ. The sophisticated column geometry was created as a dynamic geometry utilizing L-System rules and iteration principles, and then a solid substance was built using a Dynamo-PythonScript node, which acts as an interface command in Autodesk Revit. As a result, contrary to popular belief, dendriform structure geometry behaved unexpectedly and was not complicated than modern times.
Keywords: Fractal geometry; Parametric design; Computational architecture; Computer-aided design (CAD); Iterative generation method